Assembling Imperceptibility: The Material, Financial and Policy Dimensions of Combustible Cladding in Residential High-Rise. Issue 1 (1st January 2023) - Cook, Nicole; Taylor, Elizabeth J
ABSTRACT: This article focuses on the predicament of owner-occupiers and small investors presently liable for the removal of combustible cladding on build-to-sell residential high-rise. We argue that while the proliferation of combustible materials has been shaped by cost-cutting and risk-shifting by construction firms, these practices did not on their own transfer the responsibility of remediation to consumers. Examining the attempts of one densifying nation, Australia, to locate responsibility for combustible cladding through two parliamentary inquiries, we analyse witness testimonies to show how public policies encouraged materials substitution, removed on-site inspection and protected corporations from litigation. Moving beyond neoliberalism, these policy reforms leveraged information asymmetries and the material complexity of residential high-rise to create a climate of "imperceptibility" towards unsafe materials. Together, material, financial and policy dimensions intersected to enable capital accumulation through the expansion of consumer harm in high-rise housing markets. We conclude that construction materials and processes are an overlooked, yet critical domain of governance in financialised housing regimes.